Quantum dots and prion proteins: is this a new challenge for neurodegenerative diseases imaging? - Sobrova, Pavlina; Blazkova, Iva; Chomoucka, Jana; Drbohlavova, Jana; Vaculovicova, Marketa; Kopel, Pavel; Hubalek, Jaromir; Kizek, Rene; Adam, Vojtech (Prion, 2013)
A diagnostics of infectious diseases can be done by the immunologic methods or by the amplification of nucleic acid specific to contagious agent using polymerase chain reaction. However, in transmissible spongiform encephalopathies, the infectious agent, prion protein (PrP(Sc)), has the same sequence of nucleic acids as a naturally occurring protein. The other issue with the diagnosing based on the PrP(Sc) detection is that the pathological form of prion protein is abundant only at late stages of the disease in a brain. Therefore, the diagnostics of prion protein caused diseases represent a sort of challenges as that hosts can incubate infectious prion proteins for many months or even years. Therefore, new in vivo assays for detection of prion proteins and for diagnosis of their relation to neurodegenerative diseases are summarized. Their applicability and future prospects in this field are discussed with particular aim at using quantum dots as fluorescent labels.
Keywords: label; Fluorescent Dyes; Brain; Prions; Neurodegenerative Diseases; Prion Diseases; priony; kvantové tečky; Quantum Dots; molekulární modely; Models, Molecular; neurodegenerativní nemoci; Animals; lidé; prionové nemoci; neurodegenerative disease; Humans; zvířata; imaging; fluorescenční barviva; quantum dots; mozek; prion protein